Hypoxic conditions in stormwater retention ponds: potential for hydrogen sulfide emission. Issue 5 (23rd February 2019) - Chen, Liyu; Delatolla, Robert; D'Aoust, Patrick M.; Wang, Ru; Pick, Frances; Poulain, Alexandre; Rennie, Colin D.
ABSTRACT: Improper design and maintenance of stormwater ponds (SWPs) may lead to hypoxic conditions, poor water quality and the production of hydrogen sulfide (H2 S). The objective of this study is to develop a comprehensive understanding of hypoxic conditions of SWPs, with a focus on the potential for H2 S production and emission. This study was conducted at two retention SWPs in Ottawa, Canada; a problematic pond with the propensity for H2 S emission and a reference pond that did not demonstrate H2 S emission. The investigation illustrated a significant impact of low dissolved oxygen (DO) concentrations, hypoxic conditions, on the concentration of total sulfides in the water column. Both ponds were shown to periodically experience hypoxic conditions at depth, especially during summer periods with less precipitation and across longer periods of winter, ice-covered conditions. The problem pond, however, was shown to experience lower DO and longer hypoxic conditions than the reference pond in both non-ice-covered and ice-covered conditions due to greater depth and a longer hydraulic retention time. Hypoxic conditions were initiated at the deepest locations in the problem pond and subsequently were spread across the entirety of the pond under winter, ice-covered conditions. Algal biomass (Chlorophyll-a) and soluble biochemical oxygen demand concentrations were shown to not likely be significant factors in the development of hypoxia in the H2 S-generating pond. Algal blooms of colonial Chrysophyceae, Synura, a known mixotroph, were observed during ice-covered conditions in the problem pond possibly due to stress-coping mechanisms of algae.